How Do Young individuals in Vietnam Use and Perceive Satisfaction with Artificial Intelligence Algorithms on TikTok? - Nguyen Tan Khang (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
This study focuses on how young people in Vietnam use and feel satisfied with artificial intelligence algorithms on TikTok. The research paper aims to investigate and better understand how this group of young people interact and use the TikTok platform, with the integration of artificial intelligence algorithms. The study was conducted based on the results of an initial questionnaire survey on a simple random sample based on the germ development sampling method among students in Vietnam. The quantitative data is analyzed based on SPSS software. The results of the study show that the majority of young people in Vietnam have a basic knowledge and understanding of artificial intelligence algorithms on TikTok. They use them to find engaging content, watch videos, and engage with the community on the platform. However, the study also found some risks associated with using artificial intelligence algorithms on TikTok. It is a risk of privacy violation and interference with personal freedom when algorithms can track, analyze and collect the personal data of users. Thereby, the research team analyzed the data based on the use and satisfaction theory. In summary, this study has mentioned how the young public in Vietnam use and feel satisfied with the artificial intelligence algorithm on TikTok. In addition to the benefits, attention should be paid to the ethical and privacy issues associated with the use of this technology to protect the interests of users.